Co Cluster-Modified Ni Nanoparticles with Superior Light-Driven Thermocatalytic CO2 Reduction by CH4 - Mei Li; Yuhua Zhang; Na Sun; Dan Cheng; Peng Sun; Qian Zhang (Molecules)
Excessive fossil burning causes energy shortages and contributes to the environmental crisis. Light-driven thermocatalytic CO2 reduction by methane (CRM) provides an effective strategy to conquer these two global challenges. Ni-based catalysts have been developed as candidates for CRM that are comparable to the noble metal catalysts. However, they are prone to deactivation due to the thermodynamically inevitable coking side reactions. Herein, we reported a novel Co-Ni/SiO2 nanocomposite of Co cluster-modified Ni nanoparticles, which greatly enhance the catalytic durability for light-driven thermocatalytic CRM. It exhibits high production rates of H2 (rH2) and CO (rCO, 22.8 and 26.7 mmol min−1 g−1, respectively), and very high light-to-fuel efficiency (ƞ) is achieved (26.8%). Co-Ni/SiO2 shows better catalytic durability than the referenced catalyst of Ni/SiO2. Based on the experimental results of TG-MS, TEM, and HRTEM, we revealed the origin of the significantly enhanced light-driven thermocatalytic activity and durability as well as the novel photoactivation. It was discovered that the focused irradiation markedly reduces the apparent activation energy of CO2 on the Co-Ni/SiO2 nanocomposite, thus significantly enhancing the light-driven thermocatalytic activity.